Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/02640414.2016.1172724
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured sedentary time and academic achievement in schoolchildren

Abstract: This study aimed to evaluate the relationship between objectively measured total sedentary time and academic achievement (AA) in Portuguese children. The sample comprised of 213 children (51.6% girls) aged 9.46 ± 0.43 years, from the north of Portugal. Sedentary time was measured with accelerometry, and AA was assessed using the Portuguese Language and Mathematics National Exams results. Multilevel linear regression models were fitted to assess regression coefficients predicting AA. The results showed that obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
1
11
0
1
Order By: Relevance
“…When sedentary behaviour has been measured objectively, there have been inconsistent associations with academic performance. Lopes et al found no association between accelerometer measured sedentary time and academic performance [20]. However, Maher et al found that higher sedentary behaviour, measured by accelerometers, was associated with higher academic performance, [21] while Happala et al have found higher sedentary time, measured using heart rate monitors, to be associated with poorer math and reading skills [22].…”
Section: Introductionmentioning
confidence: 99%
“…When sedentary behaviour has been measured objectively, there have been inconsistent associations with academic performance. Lopes et al found no association between accelerometer measured sedentary time and academic performance [20]. However, Maher et al found that higher sedentary behaviour, measured by accelerometers, was associated with higher academic performance, [21] while Happala et al have found higher sedentary time, measured using heart rate monitors, to be associated with poorer math and reading skills [22].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it is necessary to keep in mind the relevant influence teachers have on students who appreciate their support. Increased awareness about that factor can have positive effect and can most likely redeem students' problems since studies have showen that their beliefs about own competences and school accomplishments can be changed with minimal effort (Lopes, Santos, Mota, Pereira & 2017). Further research on this subject is going to be quite significant because of the still insufficiently examined predictors of school satisfaction and satisfaction with the quality of school life, despite their relevance for cognitive, emotional and social development of preadolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity was assessed with ActiGraph GT1M accelerometers (ActiGraph™, LLC, Fort Walton Beach, FL, USA) to obtain individual objective data about each child’s activity level. Participants were instructed to wear the accelerometer on the hip (held by an elastic belt) for 5 consecutive days: three weekdays and two weekend days (Lopes, Santos, Mota, Pereira, & Lopes, 2017), removing it during water activities and sleeping time. The measurement epoch was set at 15 seconds (Ward, Evenson, Vaughn, Rodgers, & Troiano, 2005).…”
Section: Methodsmentioning
confidence: 99%